Effect of Servant Leadership and Person-Organization Fit on Employee Engagement with Job Satisfaction as Mediator Variable - Khoe Yao Tung; Monica Indriana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine effect of servant leadership and person-organization fit on employee engagement with job satisfaction as mediator variable. This research is a research with a quantitative approach. This research was conducted at XYZ Junior High School, Serpong Utara. The time of the study was carried out from January 2020 to May 2020 which involved samples from the total population studied. The population in question is full-time education staff at XYZ Junior High School, Serpong Utara who are Indonesian citizens and total 44 people. The data was processed numerically, so the data collection instrument used a questionnaire to obtain primary data. The device that will be used to perform the analysis using the partial least square-structural equation modeling (PLS-SEM) approach is the SmartPLS software. The results of the study show that servant leadership has a positive effect on employee engagement. Person-organization fit has a positive effect on employee engagement. Job satisfaction has a positive effect on employee engagement. Servant leadership has a positive effect on employee engagement mediated by job satisfaction. Person-organization fit has a positive effect on employee engagement mediated by job satisfaction.